2008
DOI: 10.1111/j.1532-5415.2008.01706.x
|View full text |Cite
|
Sign up to set email alerts
|

Amount of Social Contact and Hip Fracture Mortality

Abstract: OBJECTIVES-To study the association between amount of social contact and mortality after hip fracture in elderly participants. DESIGN-Prospective cohort.SETTING-Community residents of Baltimore, Maryland. PARTICIPANTS-Six hundred seventy-four elderly participants.MEASUREMENTS-Amount of telephone and direct personal contact between participants and their relatives and friends and mortality up to 2 years after fracture. RESULTS-Nosocial contact with friends during the 2 weeks before the fracture was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 25 publications
3
37
1
Order By: Relevance
“…Studies represent a wide range of geographical locations: Canada, Denmark, Finland, Italy, Korea, Norway, Portugal, Spain, United Kingdom and the United States of America (see Figure ). All studies collected data on post‐fracture outcomes except for two studies that also looked at pre‐fracture subjective recalled outcomes (Cobey et al, ; Mortimore et al, ). Fifteen studies primarily investigated the relationship between social factors and recovery post hip fracture, whereas four studies looked at social factors as a secondary objective (Hongisto, Nuotio, Luukkaala, Vaisto, & Pihlajamaki, ; Morghen et al, ; Orive et al, ; Sylliaas et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies represent a wide range of geographical locations: Canada, Denmark, Finland, Italy, Korea, Norway, Portugal, Spain, United Kingdom and the United States of America (see Figure ). All studies collected data on post‐fracture outcomes except for two studies that also looked at pre‐fracture subjective recalled outcomes (Cobey et al, ; Mortimore et al, ). Fifteen studies primarily investigated the relationship between social factors and recovery post hip fracture, whereas four studies looked at social factors as a secondary objective (Hongisto, Nuotio, Luukkaala, Vaisto, & Pihlajamaki, ; Morghen et al, ; Orive et al, ; Sylliaas et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In their analysis of data from the Scottish Hip Fracture Audit, Holt and coworkers found that, compared with hip fracture patients aged 50 to 59 years, the OR for death was 1.78 (95% CI, 0.95-0.33) for those aged 60 to 69 years, 3.46 (95% CI, 1.94-6.15) for those aged 70 to 79 years, 5.68 (95% CI, 3.21-10.1) for those aged 80 to 89 years, and 7.11 (95% CI, 3.98-12.7) for those aged 90 years and over [60]. Similarly, Mortimore and co-workers found that among community residents of Baltimore (USA), the RR for death was 1.13 (95% CI, 0.76-1.67) for hip fracture patients aged 75 to 84 years and 1.59 (95% CI, 1.06-2.38) for those aged 85 years and over when compared with those aged 65 to 74 years [61].…”
Section: Mortality Risk and Agementioning
confidence: 97%
“…Two studies conducted risk analyses using younger patients with hip fracture as controls [60,61]. Both studies found that the RR for death was increased in older compared with younger age groups.…”
Section: Mortality Risk and Agementioning
confidence: 99%
“…To analyze bivariate associations between baseline variables and death, 2 and t tests were used. Kaplan-Meier analysis was performed to compare unadjusted survival curves; the Wilcoxon statistic was used to assess significance.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a prospective cohort of 674 elderly, communitydwelling participants found that those with no social contact with friends or family during the 2 weeks before a hip fracture had a 5 times greater risk of death during the following 2-year period than those who had daily social contact. 2 A prospective study of 589 individuals monitored for 12 months after myocardial infarction showed that lack of a confidantnot previous depression-was associated with an adverse outcome after myocardial infarction. 1 Loneliness and living alone may be concomitant with the lack of a confidant and have been shown to be predictors of functional decline and death among older people.…”
mentioning
confidence: 99%